A Set of Variables for the Elderly Accessibility in Urban Areas - Gargiulo, Carmela; Zucaro, Floriana; Gaglione, Federica (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Until a few years ago, the elderly were considered as fragile, lonely, marginalized citizens, unable to live independently and had generally been "invisible" in studies and planning instruments that involved the governance of urban transformations. In recent years, a major focus of attention has been paid to the matter in urban development policies too (OECD, 2015), which should be oriented towards the construction of an urban model aimed at reducing the social exclusion of the elderly. For this purpose, this contribution describes a first research segment developed by the University of Naples operating unit concerning the definition of a set of variables to measure accessibility of the elderly segment of the population to the neighbourhood scale. In particular, the paper pursues a twofold objective: cognitive and methodological. Firstly, to outline the cognitive framework on the issue of urban accessibility for the elderly through a review of the main studies on this topic, the plans of sustainable urban mobility, the service plans and the governance tools for urban transformation, as well as of the most recent European best practices. The cognitive framework shall allow identifying the limits to be overcome in the reorganisation of the city. Secondly, this paper is intended to identify the set of significant variables taken from the cognitive framework and quantify its specific weight. The paper also proposes a first parameterization of the variables in the GIS environment, which refer to quantitative geo-localized data rather than collected from sample surveys, such as interviews, widely used in literature.